Painting 1977 - 1987 : The Tenth Anniversary Exhibition. (Osaka : The National Museum of Art, 1987)
Arase, Kagetoshi ; Kuwayama, Tadaaki ; Takubo, Kyoji ; Nakazato, Hitoshi ; Negishi, Yorshiro ; Hori, Kosai ; Yamamoto, Tomiaki ; Yoshimoto, Sakuji ; Lee UFan ; Borofsky, Jonathan ; Clemente, Francesco ; Martin, Agnes ; Penck, A.R. ; Rothenberg, Susan ; Salomé ; Cobo, Chema ; etc.
Painting 1977 - 1987 : The Tenth Anniversary Exhibition, The National Museum of Art, Osaka, October 3 - December 6, 1987
boek